2006
DOI: 10.1186/1471-2458-6-84
|View full text |Cite
|
Sign up to set email alerts
|

Acute health effects of the Tasman Spirit oil spill on residents of Karachi, Pakistan

Abstract: Background: On July 27 2003, a ship carrying crude oil run aground near Karachi and after two weeks released 37,000 tons of its cargo into the sea. Oil on the coastal areas and fumes in air raised health concerns among people. We assessed the immediate health impact of oil spill from the tanker Tasman Spirit on residents of the affected coastline in Karachi, Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…Pulmonary damage and subsequent respiratory compromise would not be unusual for mammals several years following exposure to an oil spill. In fact, acute and chronic respiratory symptoms were reported in humans following inhalation exposure from multiple spills, including the Prestige, Hebei Spirit, Tasman Spirit, and DWH oil spills (Suárez et al 2005, Carrasco et al 2006, Janjua et al 2006, Zock et al 2007, 2012, Sim et al 2010, Jung et al 2013, Sandler et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary damage and subsequent respiratory compromise would not be unusual for mammals several years following exposure to an oil spill. In fact, acute and chronic respiratory symptoms were reported in humans following inhalation exposure from multiple spills, including the Prestige, Hebei Spirit, Tasman Spirit, and DWH oil spills (Suárez et al 2005, Carrasco et al 2006, Janjua et al 2006, Zock et al 2007, 2012, Sim et al 2010, Jung et al 2013, Sandler et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Eye symptoms have also been reported among participants in a clean-up operation after an oil spill [8,9]. These studies have not examined long term effects of pollution on the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Zock et al [12] indicated positive relationships between the prevalence of respiratory symptoms and amount and duration of work for cleanup in a study performed in 9050 representative fishermen 14–27 months after the Prestige oil spill. In this study, the respiratory symptoms were found to persist over a period of time; Janjua et al [5] presented a negative association between the distance from the place of oil spill and irritative symptoms on the skin, in the throat and eyes, and headache by comparing the residents who lived in the contaminated area and 2 and 20 km away from the area. Lee et al [9] found that residents in highly contaminated areas suffered from a significantly high prevalence of acute health effects such as headache, nausea, dizziness, fatigue, hot flushing, insomnia, diarrhea, sore throat, cough, rhinorrhea, dyspnea, sputum, dry mouth, itchiness, red skin, eye pain, general ache, back pain, and febrile sense compared to those in less contaminated areas [9].…”
Section: Discussionmentioning
confidence: 56%
“…Some components of crude oil such as benzene have been identified as carcinogenic or probably carcinogenic to humans by the International Agency for Research on Cancer (IARC) [4]. Several studies on health effects of large-scale oil spills showed development of various physical and mental symptoms in volunteers and cleanup response teams [5-7]…”
Section: Introductionmentioning
confidence: 99%